PEMANFAATAN WISATA LOKAL MADURA SEBAGAI SUMBER BELAJAR DALAM BUKU TEKS BIPA UNTUK PEMULA - Emy Rizta Kusuma; Afiyah Nur Kayati (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the essence of local tourism on Madura Island which can be used as BIPA teaching materials for foreign speakers at the beginner level. The results of this study are BIPA textbooks at the beginner level based on the local tourism potential of Madura, especially local tourism on Mandangin Island. This study uses development research methods with four development phases, such as (1) initial investigation, (2) design, (3) realization and construction, and (4) test, evaluation, and revision. This book is develope to serve as a companion to the main teaching materials that have been provided by BIPA Kemdikbud. Therefore, BIPA teaching materials consist of various aspects of life in Indonesia.